The Extended Nutrigenomics – Understanding the Interplay between the Genomes of Food, Gut Microbes, and Human Host - Kussmann, Martin; van Bladeren, Peter (Frontiers in Genetics, 2011)
Comprehensive investigation of nutritional health effects at molecular level requires understanding the interplay between three genomes, the food, the gut microbial and the human host genome. Food genomes are researched for exploitation of macro- and micronutrients as well as bioactives, with the genes coding for bioactive proteins and peptides being of central interest. The human gut microbiota encompasses a complex intestinal ecosystem with profound impact on host metabolism. It is studied at genomic, proteomic and metabolomic level. Humans are characterized at the level of: genetic predisposition and variability in terms of dietary response and direction of health trajectories; epigenetic, metabolic programming at certain life stages with health consequences later in life and for subsequent generations; and acute genomic expression as a holistic response to diet, monitored at gene transcript, protein and metabolite level. Modern nutrition science explores health aspects of bioactive food components, thereby promoting health, preventing or delaying the onset of disease, optimizing performance and assessing benefits and risks. Personalized nutrition means adapting food to individual needs, depending on the human host’s life stage, -style and -situation. Traditionally, nutrigenomics and nutri(epi)genetics have been seen as the key sciences to understand human variability in preferences and requirements for diet as well as responses to nutrition. This article puts the three nutrition and health-relevant genomes into perspective, i.e. the food, the gut microbial and the human host’s genome, and calls for an “extended nutrigenomics” approach to build the future tools for personalized nutrition, health maintenance and disease prevention. We discuss examples of these genomes, proteomes, transcriptomes and metabolomes under the overarching term genomics that covers all Omics rather than the sole study of DNA and RNA.